Management of Colorectal Cancer Using Nanocarriers-based Drug Delivery for Herbal Bioactives: Current and Emerging Approaches - Deshmukh, Rohitas; Prajapati, Mahendra; Harwansh, Ranjit K. (Current Pharmaceutical Biotechnology, 2024)
Colorectal cancer (CRC) is a complex and multifactorial disorder in middle-aged people. Several modern medicines are available for treating and preventing it. However, their therapeutic uses are limited due to drawbacks, such as gastric perforation, diarrhea, intestinal bleeding, abdominal cramps, hair loss, nausea, vomiting, weight loss, and adverse reactions. Hence, there is a continuous quest for safe and effective medicines to manage human health problems, like CRC. In this context, herbal medicines are considered an alternative disease control system. It has become popular in countries, like American, European, and Asian, due to its safety and effectiveness, which has been practiced for 1000 years. During the last few decades, herbal medicines have been widely explored through multidisciplinary fields for getting active compounds against human diseases. Several herbal bioactives, like curcumin, glycyrrhizin, paclitaxel, chlorogenic acid, gallic acid, catechin, berberine, ursolic acid, betulinic acid, chrysin, resveratrol, quercetin, etc., have been found to be effective against CRC. However, their pharmacological applications are limited due to low bioavailability and therapeutic efficacy apart from their several health benefits. An effective delivery system is required to increase their bioavailability and efficacy. Therefore, targeted novel drug delivery approaches are promising for improving these substances’ solubility, bioavailability, and therapeutic effects. Novel carrier systems, such as liposomes, nanoparticles, micelles, microspheres, dendrimers, microbeads, and hydrogels, are promising for delivering poorly soluble drugs to the target site, i.e., the colon. Thus, the present review is focused on the pathophysiology, molecular pathways, and diagnostic and treatment approaches for CRC. Moreover, an emphasis has been laid especially on herbal bioactive-based novel delivery systems and their clinical updates.
Keywords: colorectal cancer